The problem of the personality freedom in the context of contemporary islam and christianity - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the solution of the problem of the individual freedom in the worldview context of religious philosophical systems of Christianity and Islam.